Android-Based Information System Of Online Teaching Services With Geo-Location Determination - Bambang Riyono; Widia Rifkianti (bit-Tech, 2018)
The information system of online teaching services with geo-location determination is a system that brings together and arranging meetings between private tutors and people looking for private tutors through Android application supported with geo-location. People can go looking for tutors of related subject for specific time of meeting and location, and then the system will search tutors with matched time of availability within nearest location radius. In addition, students can organize or plan a learning meeting session with the teacher through the application. This information system is a client-server based where the built application consists of Android applications running on the client environment and web applications running on the server environment. Mobile/client applications are used by end-users to search and organize learning session. Web applications serves as web services and interfaces for administrator to manage master data, view user and transaction data, print reports, and respond to complaints from end-users. The programming language used in building this information system is the Java programming language for mobile applications and PHP for web applications and web services. And using MySQL as the database.